(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
The study evaluated aspects of population dynamics of Pagruscaeruleostictus and the implications for management in Sierra Leone, needed to support efficient management plans of its fishery. 12, 729 specimens of Pagruscaeruleostictus were collected off Sierra Leone from January-November, 2016 using randomized sampling techniques on-board demersal trawler. Analysis of population dynamics employed methods fitted in FiSAT II software using pooled length-frequencies. Estimated growth parameters were asymptotic length (L∞ = 34.48cm) and weight (W∞ = 4693.6g), growth rate (K = 0.29yr-1), growth performance index (ɸ = 2.54), growth exponent (b = 3.09), theoretical age (to = -0.8years) and life-span (tmax = 9.50years). The instantaneous fishing mortality rate (F = 0.40yr-1) climaxed the optimum fishing mortality rate (Fopt = 0.30yr-1) and slightly below the limiting fishing mortality (Flimit = 0.51yr-1) whereas natural mortality rate (M) gave 0.76yr-1. Besides, the estimated current exploitation rate (Ecurrent) exceeded the estimated sustainable level of exploitation (E50 = 0.39yr-1) but below the estimated maximum allowable exploitation point (Emax = 1.10yr-1). Further, the length (Lm50 = 23.00cm) and age (tm50 = 4.60years) at first maturity climaxed the length and age at first capture (Lc50 = 21.64cm, tc50 = 3.8years,), length and age at first recruitment (Lr = 13.00cm, tr = 2.4years). Results portrayed slow and isometric growth, median life-span and high survival of a continuously recruited spawning stock of Pagruscaeruleostictus. Also, the stock suffered growth overfishing, moderate fishing pressure and overexploition, implying the need for management to recalibrate measures for rational exploitation. Res. Agric., Livest. Fish.7(3): 517-531, December 2020